2015
DOI: 10.1080/10406638.2015.1005242
|View full text |Cite
|
Sign up to set email alerts
|

Profiles and Sources of PAHs in Sediments from an Open-Pit Mining Area in the Peruvian Andes

Abstract: The Peruvian Andes are one of the most productive areas for mining and therefore also one of the most exposed to these sources of pollution. This article reports the characterization of Polycyclic Aromatic Hydrocarbons (PAHs) in sediments of Cerro de Pasco area (Peru) located close to a large open-pit mine and, in recent years, several reports have provided evidence of environmental contamination and related health problems. Investigations were carried out into the fifteen PAHs identified by the US-Environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Finally, the points with the greatest contamination in water (A3) are closely related with mining activity and waste disposal, which is in good agreement with the conclusions of Bianchini et al [10] and Orecchio et al [11], as point 2 is located near to the mining company Atacochaas well as point 6 is near the Rumillana dump.…”
Section: 1about the Case Studysupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, the points with the greatest contamination in water (A3) are closely related with mining activity and waste disposal, which is in good agreement with the conclusions of Bianchini et al [10] and Orecchio et al [11], as point 2 is located near to the mining company Atacochaas well as point 6 is near the Rumillana dump.…”
Section: 1about the Case Studysupporting
confidence: 88%
“…The results showed that high concentrations of Al, Mn and Pb were present in the water near the mines, and in consequence, in drinking water within the zone. Another research considered was Orecchio et al [11]in which Polycyclic Aromatic Hydrocarbons (PAHs) were analyzed and measured in relation to their toxicity to organisms, animals and, in consequence,to human health. All samples were collected in the same stations of the previous study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is a good indication that the PAHs in the sediments are derived from pyrolytic sources rather than from leakage of petroleum derived fuels and lubricants from urban off. Similar source apportionments were reported for mangrove sediments, North Persian Gulf [44] and open-pit sediments from a mining area at Cerro de Pasco, Andes [45].…”
Section: Source Apportionment Of Pahs Found In the Msunduzi River Basinsupporting
confidence: 56%
“…The US Environmental Protection Agency (EPA) has highlighted 16 unsubstituted PAHs as priority pollutants that need monitoring. Numerous investigations found that PAHs are widely distributed in the environmental media such as sediments, 10 agriculture soil, 11 urban soil, 12 roadside soil, 13,14 industry-affected soil, 15,16 dump sites, 17 and mine-impacted soil. [18][19][20] Soil pollution in the coal mine area is mainly ascribed to coal exploitation, processing, and utilization.…”
Section: Introductionmentioning
confidence: 99%